Unmanned aircraft propulsion system suitable for operations within spatially limited areas - Urban, Daniel; Hylmar, Karel; Kusmirek, Stanislav; Hanakova, Lenka; Socha, Vladimir (2023 International Conference on Military Technologies (ICMT), 2023)
The subject of this research is the development of ducted propulsion systems as replacements for traditional propeller propulsion systems intended for unmanned aircraft (UA). With the increasing number of operating UA and level of their automation, new possibilities for using UA in a number of applications are emerging. According to current legislation, one of the main limitations of the use of UA to date is the insufficient safety of UA operations over populated areas. Current UA equipped with propeller drive units do not achieve the required safety due to the rotating propeller blades. Ducted propulsion systems eliminate this shortcoming and provide other advantages that find their place mainly in conditions with space limitations. It is therefore necessary to find an optimal solution to these urban traffic problems. It is thus offered as a safety solution when operating in shared spaces near non-involved persons. The proposed specifications in this study are tested and the data subsequently compared with selected reference propeller drives from the point of view of energy consumption and generated thrust value. The aim of this study is to propose an optimal operational specification of the EDPS engine, suitable for UA operation from the point of view of better energy consumption and generated thrust compared to propellant systems. The results of the study prove that EDPS propulsion systems generate more thrust with lower total energy consumption than conventional propeller systems.